Gut microbiome, a novel precision medicine biomarker for hepatocellular carcinoma - Chen, Pin-Jung; Devkota, Suzanne; Shiao, Stephen; Hendifar, Andrew; Yang, Ju Dong (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality worldwide. Although immune checkpoint inhibitors (ICIs) have transformed systemic therapy, durable responses are achieved in only a subset of patients, highlighting the need for reliable predictive biomarkers. The gut–liver axis, a bidirectional network linking intestinal microbiota, microbial metabolites, and hepatic immune pathways, has emerged as a key regulator of liver immunity and tumor progression. Growing evidence indicates that the gut microbiome modulates ICI efficacy by shaping immune activation, cytokine signaling, and drug metabolism. This review summarizes current insights into how gut microbial composition and metabolites influence immunotherapy outcomes in HCC and discusses microbiome-targeted strategies, including fecal microbiota transplantation (FMT), prebiotics, probiotics, and dietary interventions. Further research and clinical validation are needed before these insights can be effectively integrated into HCC management.